Sleep disturbances and Alzheimer’s disease: a multiscale approach from exposome to neurobiology and precision medicine - Masoud Tahmasian; Jorik D. Elberse; Reihaneh Ahmadi; Wen Liu; Ivana Rosenzweig; Sarah Genon; Simon B. Eickhoff; Bryce A. Mander (GeroScience, 2026)
Sleep disturbances and Alzheimer’s disease (AD) are interconnected public health challenges. However, the underlying mechanisms of their complex relationships remain elusive. Here, we propose a hypothetical integrative, stream-like model outlining how external and internal exposome factors accelerate brain aging, thereby exacerbating circadian dysregulation, orexin-mediated hyperexcitability, metabolic imbalance, and inflammaging. These changes can lead to increased sleep fragmentation and reduced slow-wave sleep, triggering widespread neuroinflammation, glymphatic dysfunction, and the accumulation and dissemination of beta-amyloid and tau peptides. These processes collectively accelerate synaptic dysfunction, neuronal loss, and cognitive decline. We also highlight recent neuroimaging evidence that elucidates the neural substrates underlying the relationship between poor sleep and AD. Moreover, tackling their shared burden necessitates the active consideration of inter-individual variability in vulnerable populations through artificial intelligence and computational approaches, aligning with the core tenets of precision medicine. We hope this review encourages clinicians to prioritize monitoring and treating sleep disturbances to reduce the incidence, severity, and consequences of dementia in the general population.